The subaltern discourse of the Philippine policy on climate change "mimicked without difference"? - Cordovez, Faye Louise H.; Enales, Sharmaine Joy P.; Espada, Jerico O.; Sanglay, Richmond A.; Oquendo, Rene Alvin F. (2015)
The aim of this study is to determine the power relations exhibited in the Philippine policy on climate change vis-á-vis the Western modelled frameworks on climate change suggestive on the United Nations Framework Convention on Climate Change (UNFCCC). In light with this, the researchers are interested on identifying the symptomatic claims for a subaltern policy on climate change in the Philippines. Employing Homi Bhabha's
In order to achieve the objectives of this study, the researchers used a 'qualitative content analysis with three (3) levels of coding' on analyzing raw data. In this method, two set of data are used including (1) direct responses from two in-depth interviews from the Climate Change Commission and the Environmental Management Bureau (EMB) of the national office of the Department of Natural Resources and (2) the purposively selected jurisprudence related to the Philippine policy on climate change composed of twenty (20) documents. The set of data was subjected under crucial coding procedures up until various categories and themes emerged in the analysis. From these themes and categories, the researchers established relationship between and among them to address the research objectives.
The results of the study show that there are indirect and subtle manifestations of power dynamics between the Philippine policy on climate change vis-á-vis the Western modelled frameworks on climate change. This is indicative on the reciprocated influence of both frameworks in climate change policy, the ambivalent adaptation/mitigation-economic development relationship, the proliferation of an intensifying climate change condition, the overemphasis on the idea of climate resiliency and adaptation measures and others. In addition, data suggests that the Philippine policy on climate change is a 'mimicked without difference' subaltern policy that is constructed by the homogenizing discourse of international framework as one having a marginalized, minoritized and weak subject-position. Its 'mimicked' identity is simply a product of the assimilation and incorporation of the homogenizing discourses of the international framework.
Undergraduate thesis (B.A.S.S. Political Science)-- Univeristy of the Philippines, Tacloban.